Changing trends in cancer incidence of upper aerodigestive tract and stomach in Japanese alcohol‐dependent men (1993‐2018) - Akira Yokoyama; Tai Omori; Tetsuji Yokoyama (Cancer Medicine)
Abstract Background Esophageal squamous cell carcinoma (ESCC), head and neck SCC (HNSCC), and gastric adenocarcinoma (GA) are frequently detected at an early stage using endoscopic screening in Japanese alcohol‐dependent men. Methods We performed endoscopic screening with esophageal iodine staining and oropharyngolaryngeal inspection in 7582 Japanese alcohol‐dependent men (40‐79 years) during 1993‐2018, and retrospectively investigated their initial screening results. Results The 2008‐2018 screening showed lower detection rates for ESCC (2.6% vs 4.0%, P = .0009) and GA (0.5% vs 1.4%, P < .0001) for all age brackets, compared with the 1993‐2007 screening. The HNSCC detection rate did not change (1.0% vs 1.1%). Multiple logistic regression analyses showed that the 2008‐2018 screening had a reduced OR (95% CI) for ESCC (0.34 [0.25‐0.47]) and GA (0.19 [0.10‐0.35]), compared with the 1993–2007 screening. The reduction in H pylori infection is probably the main reason for the decrease in GA detection over time. Declining trends in pack‐years and gastric atrophy and increasing trends in age and body mass index (BMI) were found over time. The presence of advanced gastric atrophy increased the risk for ESCC as well as GA. The inactive heterozygous aldehyde dehydrogenase‐2*1/*2 genotype was a strong risk factor for ESCC, HNSCC, and GA. Fewer pack‐years and a larger BMI decreased the ESCC risk. However, these confounders cannot fully explain why the incidence of ESCC has decreased markedly over the recent decade. Conclusions The detection rates of ESCC and GA have markedly decreased during the past decade in the alcohol‐dependent population. The enigmatic declining trend of ESCC warrants research on this topic.